Dietary rosemary extract modulated gut microbiota and influenced the growth, meat quality, serum biochemistry, antioxidant, and immune capacities of broilers - Liu, Yang; Li, Chuang; Huang, Xuan; Zhang, Xu; Deng, Ping; Jiang, Guitao; Dai, Qiuzhong (Frontiers in Microbiology, 2022)
After the legislative ban on the utilization of antibiotics in animal feed, phytochemical substances gained increasing attentions as replacers of antibiotics because of their bioactivities and safety. The present study aimed to investigate the influences of dietary rosemary extract (RE) on growth performance, meat quality, serum biochemistry, antioxidant and immune capacities, and gut microbiota composition of broilers. By exploring connections among RE, physiological characteristics, and key microbiota, we sought to provide evidence for the utilization of RE in poultry feed. A total of 560 1-d-old female AA broilers were randomly separated into 5 treatments, and were fed basal diet supplemented with 0, 250, 500, 750, and 1000 mg/kg RE, respectively. Results showed that both 500 and 750 mg/kg RE reduced broilers feed to gain ratio from 1-21 d (P = 0.018). All dietary RE reduced the cooking loss of breast muscle (P < 0.01), and 500 and 1000 mg/kg RE reduced the cooking loss of thigh muscle (P = 0.045). 500 mg/kg RE reduced ALB, TCHO, HDL-C, and LDL-C, and 750 mg/kg RE reduced GLU, TP, ALB, UA, TG, TCHO, HDL-C, and LDL-C (P < 0.01). 250, 500, 750 and 1000 mg/kg RE increased the T-AOC, GSH-Px, SOD, CAT, IL-2, IgA, IgG, and IgM levels (P < 0.01), and decreased serum MDA levels (P < 0.01). RE at 750 mg/kg showed similar effects in growth performance, meat quality, antioxidative and immune capacities, but better influences on serum biochemical indexes of broilers compared with 500 mg/kg. Further analysis was conducted to investigate the effect of 750 mg/kg dietary RE on the gut microbial composition of broilers, and the result showed that 750 mg/kg RE reduced relative abundances of g_Lachnoclostridium, g_Escherichia_Shigella, and g_Marvinbryantia (P < 0.05, LDA score > 2), which were negatively correlated to antioxidative and anti-inflammatory parameters (P < 0.05). In conclusion, 750 mg/kg dietary RE was shown having certain beneficial effects on growth performance and meat quality, and hypolipidemic and hypoglycemic effects in broilers. Further dietary RE improved the antioxidant and immune capacities, which was partially attributed to the reduced abundances of certain pathogenic bacteria of broilers.